PENERAPAN MODEL PEMBELAJARAN ROTATING TRIO EXCHANGE (RTE) UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN MATERI UPAYA-UPAYA PENEGAKAN HAM DI INDONESIA (Faculty of Social Science, Universitas Negeri Semarang, 2015)
The purpose of this research is to improve the quality of learning through the application of the Rotating Trio Exchange (RTE) model on the Material of Human Rights Enforcement in Indonesia. The study wasconducted in X IPA 4 and X IPA 8 graders of SMA Negeri 1 Pati Academic Year 2014 / 2015. The characteristic of students in both classes is balanced in terms of the dynamics of the activity and the value of learning outcomes that all have passed the learning mastery (100% passed).Implementation of the actions carried out in three cycles (cycle I, II, and III), each cycle lasts for 135 minutes (3 x 45 minutes). The design of Class Action Research uses the models of Kemmis and Taggart (1988) whose implementation consists of four steps: (1) planning; (2) implementation; (3) observation; and (4) reflection.The results of the implementation on the first cycle is not in line with expectations, as one indicator of the knowledge domains and one indicator of the skill domains shows a lower value or not balanced with other indicators. The average classical learning mastery in this cycle is above the passing grade (80). TQM indicators of these two classes is balanced, that is 684 for X IPA 4 and 679 for X IPA 8. The mean of TQM cognitive formation of both classes is 24.87%, skills is 49.081, and attitudes is 26.049%. In the second cycle, an improvement is carried out in the discourse of knowledge and skills of 7.8. This is influenced by the dynamics of student involvement equalization model which is evenly and alternately. In the third cycle, the two classes showed a different increase in quality, class X IPA 8 showed positive improvement, while Class X IPA 4 shows a fluctuative increase. The increase is relatively small, nevertheless indicates a significant RTE models to improve the quality of classical learning. The use of appropriate learning models is one of the factors that teachers can do to improve the quality of learning that is shown by the increase in student learning outcomes.